Draft Annual Plan 2008-09 (Sectoral Plans) Volume-II Government of Nagaland - Planning Commission (Planning Commission, 2007)
Set-up in 1,968 as an evaluation and monitoring under the Planning and Co-ordination Department, the unit is now a full fledged Directorate with District Evaluation Offices in eight districts at Kohima, Mokokchung, Mon, Phek, Tuensang, Wokha, Zunheboto and Dimapur. Functions: The main function of the Evaluation Directorate is to undertake independent unbiased evaluation studies on implementation of the various schemes/programmes of the Government and suggest ways and means to bring about improvement in the formulation and execution. Through the two aspects (i) retrospective-assessment of the achievement of the programmes and (ii) prospective -what should be done to improve the programmes and through cost-benefit analysis the evaluation studies aid decision making and provide insight into the programmes.
Planning and Co-ordination Department Government of Nagaland